Arnold-Chiari Syndrome – a review - Pociecha, Agnieszka; Kozikowska, Marta; Kmak, Bożena; Szot, Anna; Górska, Magdalena; Stuglik, Nikola; Hitnarowicz, Anna; Janocha, Aleksandra; Jerzak, Aneta (Journal of Education, Health and Sport, 2024)
Arnold Chiari syndrome, also known as Chiari malformation, is a group of deformations of the posterior cranial fossa and hindbrain, consisting in the lowering of the cerebellum or its tonsils towards the occipital foramen. This leads to a reduction in the volume reserve within the foramen magnum, pressure on surrounding structures and obstruction of the flow of cerebrospinal fluid. The process is most often asymptomatic. Symptoms include headaches, neck pain, but also fainting, sinus bradycardia, coordination disorders and many others. Chiari malformation is often diagnosed incidentally. The basis of diagnosis is the detection of characteristic morphological features in magnetic resonance imaging. Surgical treatment is successfully used among patients with severe Arnold-Chiari syndrome and progression of clinical symptoms. Materials and methods Literature included in the PubMed, BioMed Central and Polish Medical Platform databases searched by means of the words such as Gamma Knife, CyberKnife, radiosurgery, stereotactic radiotherapy. Sources quoted in selected works were also used. Summary Arnold-Chiari malformation is often discovered incidentally. If the features observed on MRI suggest the above diagnosis, the patient should be referred to a neurologist. After excluding other possible causes of the imaged morphological features and performing a dedicated magnetic resonance imaging examination, the neurosurgeon decides whether to qualify for the procedure. In a selected group of patients, significant improvement can be expected after surgical treatment.